Expressão de Qa-2 e sua relação com o infiltrado linfocítico e a diferenciação celular em dois modelos murinos de adenocarcinoma mamário - Istefani Luciene Dayse da Silva (2017)
Qa-2, described as the murine homologue of Human Leukocyte Antigen G, plays a controversial role in neoplasms, favoring or harming tumor development. Thus, the aim of the present study was to characterize the expression of Qa-2 in two experimental models of breast cancer: Ehrlich solid tumor and 4T1 tumor cells. Experiments with the two models were performed independently, where for Ehrlich, was performed the evaluation of the serum and tissue expression of Qa-2 and the histopathological evaluation of the peritumoral inflammatory infiltrate and the immunohistochemical characterization of the lymphocytic infiltrate. In the 4T1 model, the evaluation of the serum and tissue Qa-2 expression was also performed, followed by the evaluation of the Qa-2 expression in the cell line derivation model, in order to evaluate the effects of the epithelial-mesenchymal transition in the expression of Qa-2. Inhibitors of Src kinases, which are implicated in the mesenchymal epithelial transition process, were used in vitro to investigate their effects on Qa-2 expression. Also, through gene cloning, 4T1 cells overexpressing Qa-2, were obtained, and its effects on tumor development and the onset of metastases were evaluated in vivo. Our results showed different Qa-2 expression profiles for each tumor model studied. The 4T1 tumor model underwent a progressive reduction and Ehrlich solid tumor, there was an increase in the intermediate time of tumor development. Furthermore, in the 4T1 model it was possible to show that the reduction of Qa-2 expression is related to epithelial-mesenchymal transition and characteristics of cancer stem cells. The findings obtained in the experiment with cells overexpressing Qa-2, showed reduction of the tumor growth, associated to reduction of the metastases. These findings lead us to conclude that Qa-2 plays an inhibitory role in tumor development in Ehrlich solid tumor models and 4T1 tumor cells, associated with lower tumor aggressiveness.